On the appraisal criteria in Chekhov's works - Smolkin, M. (Literatūra, 1970)
The problem of the appraisal criteria is one of the main problems in the ethics and aesthetics of each writer. The selection of phenomena is impossible without estimating them on a scale of social and moral value. In order to reveal the aesthetics of a writer in its profound completeness it is necessary to point out the author's variety of criteria in evaluation of man, society, art.The three-dimensional phenomena in the aesthetics of the writer is revealed. The three-dimensional evaluation covers his understanding of man, reality, as well as the versatility of his style.
Keywords: -